El desarrollo sostenible, principio y objetivo común de la sociedad y el mercado, en la UE de nuestros días - Yábar Sterling, Ana (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2004)
Sustainable development, explicit goal of the EU introduced on Amsterdam Treaty (art. 2), is a three dimension principle—economic, social and environmental—which aims to guaranty a better life quality for present and future Union population, grasping several EU internal policies, at least the environmental, economic and social policies. Environmental EC actions implemented all along the nineties —and part of the eighties—, were permeated by sustainable development objective; that principle was formally mentioned as such in the Fifth Environmental Programme and it is also the case for the EU environmental policy stricto sensu, ahead. Therefore, in this scope the principle is well established and shows a high degree of maturity in subjects as the management of natural resources, the production and the consumption of energy, etc. The economic face of sustainable development principle acquires true spread in the UE, latter on —at the beginning of XXI century— after the agreements adopted in the European Councils of Lisbon and Gotemburgo and, still more clearly, after the adoption of EU Strategy of Sustainable Development formulated by the Commission on 2001. The structural reforms suggested and stimulated in the markets (labor, financial and of several products) of the States members, from the EU institutions is one of the best indicators on the actual economic relevance of the EU sustainable development perspective. The social dimension of sustainable development principle, offers at present in the EU the minor level of progress. Nevertheless, several EU proposals recently designed by the Commission reinforce the third perspective of that principle; those recent proposals aims mainly to international eradication of poverty, or to improve the fairness in the regional distribution of growth increasing the financial resources canalized to the third world countries’s growth.